The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9nr00176j
|View full text |Cite
|
Sign up to set email alerts
|

Repeatable and metal-independent nanotransfer printing based on metal oxidation for plasmonic color filters

Abstract: A repeatable metal-independent transfer printing method is developed to repeatedly transfer nanopatterns for fabricating plasmonic color filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Advantageously, the proposed method allows transfer to be conducted at low temperature that is independent of the employed material. In our previous works, we found that Au, Al, and Ag nanostructures can be melted and oxidized below 150 °C, 30,31 which highlights the importance of performing transfer at low temperature. Consequently, we selected PMMA as a flexible substrate with a low T g and used DSC analysis to show that the T g of the PMMA film with the thickness of 150 μm (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Advantageously, the proposed method allows transfer to be conducted at low temperature that is independent of the employed material. In our previous works, we found that Au, Al, and Ag nanostructures can be melted and oxidized below 150 °C, 30,31 which highlights the importance of performing transfer at low temperature. Consequently, we selected PMMA as a flexible substrate with a low T g and used DSC analysis to show that the T g of the PMMA film with the thickness of 150 μm (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The obtained spectra featured only the typical peak of Au at the interface between Au and PMMA. Peaks due to Au oxidation were not observed, as transfer was conducted at 110 °C, that is, at a temperature higher that the T g of the PMMA film and lower than the oxidation temperature of Au (150 °C) . It was concluded that above its T g , the deformed PMMA film covers the interface of the deposited materials, which are thus physically detached from the donor polymer stamp and transferred onto the PMMA substrate (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stamping method provided the method for fabrication of various structural graphene-based hybrid arrays such as the line, grid and dot arrays, which structures were evaluated to find the optimal structure for differentiation of MSCs. In addition, using the stamping method, the metallic nanopattern array was developed through the combined use of stamping method and nano-transfer printing technique (Hwang et al, 2019 ). For achieving this goal, authors prepared the nanopattern template using the stamping method, and then, metal ions were deposited on the prepared nanopattern template.…”
Section: Nanoarray To Monitor Stem Cell Differentiation Based On Electrochemical Techniquementioning
confidence: 99%
“…Different kinds of noble metal NW arrays (Pd, Pt, Au, and Ag; 100 nm width × 200 nm pitch × 20 nm thickness) were fabricated by depositing the corresponding metals onto the patterned polymer on the PET film by electron beam evaporation (Daeki Hi-Tech Co., Ltd., Korea) at a rate of 1 Å s –1 . Subsequently, nanowelding of the metal NW arrays was implemented using an abovementioned method at a pressure of 5 bar and a temperature of over 160 °C for 10 min by thermal nanoimprinting (Hutem Co, Korea).…”
Section: Experimental Sectionmentioning
confidence: 99%